2016
DOI: 10.1007/s10565-016-9368-3
|View full text |Cite
|
Sign up to set email alerts
|

Benzophenone-3 increases metastasis potential in lung cancer cells via epithelial to mesenchymal transition

Abstract: Exposure to compounds with cancer-potentiating effects can contribute to the progression of cancer. Herein we have discovered for the first time that benzophenone-3 (BP-3), a chemical used as sunscreen in various cosmetic products, enhances the ability of lung cancer cells to undergo metastasis. The exposure of the lung cancer cells to BP-3 at non-toxic concentrations significantly increased the number of anoikis resistant cells in a dose-dependent manner. Also, BP-3 increased the growth rate as well as the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Cancer metastasis is the multistep process of cancer cells spreading from their original site to other distant sites of the body [ 32 – 34 ]. During metastasis, cancer cells in an anchorage-independent condition are likely to die in the process of anoikis, a detachment-induced apoptosis; however, metastatic cells utilize several mechanisms to escape anoikis and consequently grow at distant sites [ 22 , 35 , 36 ]. Among several potentiating factors of metastasis, the transition of epithelial to mesenchymal phenotype, known as EMT [ 6 , 37 , 38 ], has garnered most attention [ 39 – 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer metastasis is the multistep process of cancer cells spreading from their original site to other distant sites of the body [ 32 – 34 ]. During metastasis, cancer cells in an anchorage-independent condition are likely to die in the process of anoikis, a detachment-induced apoptosis; however, metastatic cells utilize several mechanisms to escape anoikis and consequently grow at distant sites [ 22 , 35 , 36 ]. Among several potentiating factors of metastasis, the transition of epithelial to mesenchymal phenotype, known as EMT [ 6 , 37 , 38 ], has garnered most attention [ 39 – 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anchorage-independent growth was determined by the soft agar colony-formation assay, modified from Phiboonchaiyanan PP. et al’s method [ 22 ]. H460 cells were pre-treated with phoyunnanin E at non-toxic concentrations (0–10 μM) for 48 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, it was shown that in ovarian cancer, the activation of EMT is associated with chemoresistance, the latter of which can cause cancer recurrence and metastasis following conventional treatment against ovarian cancer ( 25 , 26 ). Additionally, benzophenone-3 has been demonstrated to increase metastasis potential in lung cancer via the induction of EMT ( 27 ). Following full review of the EMT data in the present study, together with the cell migration and invasion assays, it is concluded that TRIM59 may promote metastasis in medulloblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Like BPA, OxBZ and related compounds can form mutagenic and genotoxic metabolic byproducts by photo-oxidative stress responses [9] or DNA-adduct formation involving bio-activation by cytochrome P450 enzymes [11,12]. Oxybenzone and other benzophenones also increase tumor metastasis potential by inducing proliferation in cancer cell lines via estrogen-mediated [13,14] and non-estrogenic mechanisms [15].…”
Section: Introductionmentioning
confidence: 99%